Protikladný vývoj trendů incidence kapavky a syfilis ve východočeském regionu - 30 let surveillance - Salavec, M; Boštíková, V; Prášil, P; Smetana, J; Spliňo, M; Chlíbek, R; Louda, M; Sleha, R; Stěpánová, V; Boštík, P (Epidemiologie, mikrobiologie, imunologie, 2014)
The epidemiology of selected sexually transmitted diseases in the Czech Republic has been carefully evaluated for many years. Data from 1981-2011 for eastern Bohemia shows a sharp decrease in the incidence of gonorrhea in 1993-1994 and a very low incidence thereafter with a slightly higher prevalence in males. However, syphilis and genitourinary infections with Chlamydia trachomatis show entirely opposite trends. Also, for the similar number of diagnostic tests performed, Chlamydia had a 10 fold higher rate of positive results. This underscores the changing epidemiology of sexually transmitted infections (STI) and necessity for adapting the reporting algorithms accordingly.
Keywords: Syphilis; Česká republika; chlamydiové infekce; Incidence; prevalence; lidé; Female; gonorea; mužské pohlaví; Prevalence; Male; syfilis; incidence; Gonorrhea; Czech Republic; ženské pohlaví; Chlamydia Infections; Humans